The effect of placental location on placental weight and infant birth weight of pregnant mothers: a cross-sectional study. - R. Behzadmehr; M. Ghalandarzadeh; M. Afshari; M. N. Moghadam; R. Behzadmehr (Pediatric Anesthesia and Critical Care Journal, 2020)
Introduction The placenta is considered to be the most vital organ of the infant. The intrauterine fetal growth and development indicates a harmony between the fetus, placenta, and mother. Studies show that placenta has different effects on maternal and neonatal outcomes. This study aimed to investigate the effect of placenta location on placental weight (PW) and infant birth weight (IBW) in pregnant mothers. Material and Methods This descriptive study was performed on 370 pregnant mothers and their newborns referring to Amir-al- Momenin Hospital in Zabol, south of Iran from October to March 2018. The data collection tool included a researcher-made checklist consisting of two parts: maternal demographic information and infant information. The placenta location was determined by ultrasound and recorded by a radiologist and the Apgar's score was measured by an obstetrician in the delivery room. The collected data were then analyzed using descriptive and analytical tests. Results The mean± SD of maternal age, maternal BMI, Apgar score, and IBW was 30.39±5.44. 25.24 ± 4.54, 9.65 ± 0.65, 3244.61 ± 204.116 gr, and 548.83± 104.65 gr, re- spectively. Most of the infants were male (50.3%). The placenta was mainly located in the fundal portion of the womb (44.9%). Results showed no significant relation- ship between the placental location and IBW (p = 0.555). However, the results showed a significant relationship between the placental location and PW (p = 0.028). Conclusion Since the results of this study indicate the relationship be- tween placental location and PW and infants' gender, spe- cialists are recommended to consider placental location as a factor affecting PW.